WASTE GENERATED DURING THE POLYETHYLENE PRODUCTION PROCESS AND THEIR RECYCLING METHODS (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the types, origins, and properties of waste generated during the production of polyethylene using modern SCLAIRTECH technology, as well as methods for their utilization, recycling, and neutralization. The study identifies the sources, composition, and environmental risks of various waste streams, and evaluates the potential for their reuse as secondary raw materials. The results show that approximately 98% of the production waste can be repurposed either as an energy source or as industrial feedstock, highlighting the compatibility of SCLAIRTECH technology with sustainable, low-waste manufacturing practices. The article includes graphical and tabular data illustrating waste volumes, composition, and management mechanisms, making it a valuable resource for addressing contemporary environmental challenges in polymer production.